2015
DOI: 10.1039/c4an01860e
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence prediction in oral cancers: a serum Raman spectroscopy study

Abstract: High mortality rates associated with oral cancers can be primarily attributed to the failure of current histological procedures in predicting recurrence. Identifying recurrence related factors can lead to improved prognosis, optimized treatment and enhanced overall outcomes. Serum Raman spectroscopy has previously shown potential in the diagnosis of cancers, such as head and neck, cervix, breast, oral cancers, and also in predicting treatment response. In the present study, serum was collected from 22 oral can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 46 publications
1
45
0
Order By: Relevance
“…In 2006, Popp et al used UV-RRS (244 nm excitation) to study the cryoprecipitated human plasma of patients with thrombotic microangiopathy, a pathology that results in thrombosis (formation of a clot inside a blood vessel). 185 At the selected wavelength, Raman signals of aromatic amino acids and proteins were selectively enhanced and the study demonstrated considerable variations in the intensities of bands at 1551, 1615, and 1650 cm -1 (associated with the amide II vibration, in-plane stretching vibrations of aromatic amino acids, and the 174 Reproduced with permission ß2014, Macmillan Publishers Ltd: Scientific Reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2006, Popp et al used UV-RRS (244 nm excitation) to study the cryoprecipitated human plasma of patients with thrombotic microangiopathy, a pathology that results in thrombosis (formation of a clot inside a blood vessel). 185 At the selected wavelength, Raman signals of aromatic amino acids and proteins were selectively enhanced and the study demonstrated considerable variations in the intensities of bands at 1551, 1615, and 1650 cm -1 (associated with the amide II vibration, in-plane stretching vibrations of aromatic amino acids, and the 174 Reproduced with permission ß2014, Macmillan Publishers Ltd: Scientific Reports.…”
mentioning
confidence: 99%
“…These changes were attributed to DNA and variable protein content in the groups. 174 Researchers from Guangdon, China have carried out similar Raman work regarding cancer detection in plasma. They used the drop-coated deposition technique on plasma from patients with colorectal cancer (15 patients) and from normal healthy controls (21 volunteers).…”
mentioning
confidence: 99%
“…The metabolites in the biofluids of the patients with cancers are different from the normal subjects, due to the amino acid metabolism, cell apoptosis and tumor necrosis, which can be used for the cancer detection as the biomarkers [10, 12]. The serum or plasma have been selected as the samples for the cancer detection and diagnosis by Raman spectroscopy successfully because the serum or plasma is easily collected and mostly contains some vital biomarkers generated by cancers [10, 15, 21, 22]. Rekha et al [21] reported that the plasma Raman spectra of the oral premalignant and malignant conditions were different from the normal condition, and could be utilized to diagnose the oral premalignant and malignant conditions with the sensitivity and specificity of above 80.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Rekha et al [21] reported that the plasma Raman spectra of the oral premalignant and malignant conditions were different from the normal condition, and could be utilized to diagnose the oral premalignant and malignant conditions with the sensitivity and specificity of above 80.0%. Serum Raman spectroscopy had the potential not only in the diagnosis of oral cancers, but also in the prediction of treatment responses [22]. Accordingly, the serum was the sample of the choice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tumor biomarkers are molecules produced specifically or in excess of normal tissue by the pre-malignant cell, tumor cell or recurrent cancer cell, which may accumulate and are released into the circulation. These can help in the diagnosis, monitoring and prognosis of the treatment response (6). It is known that alphafetoprotein (AFP), cancer antigen (CA)-125, prostate-specific antigen (PSA) are used as serum biomarkers for the diagnosis, monitoring and the prognosis of liver, ovarian and prostate cancer, respectively.…”
Section: Introductionmentioning
confidence: 99%